Chromosomal microarray on product of conception in early pregnancy loss: A case report - Snehal Mallakmir; Gauri Mulgund; Rashid Merchant (Apollo Medicine)
Introduction: Early recurrent pregnancy loss (RPL) has many etiologies but even after routine investigations, in up to 50% of cases the cause may not be found. Evaluation of products of conception (POC) is very important to detect chromosomal abnormalities associated with RPL. Various studies have now demonstrated the benefits of chromosomal microarray analysis (CMA) compared to conventional cytogenetic analysis in managing RPL. Case Report: We report a couple with two early pregnancy losses. The cytogenetic analysis by CMA was carried out in the POC from the second RPL at 6 weeks' gestation. The CMA revealed complex structural chromosomal abnormalities including the 16.3 Mb microdeletion involving chromosome 10 within the 10q26.11-q26.3 segment, indicating monosomy for this region, and the 57.4 Mb microduplication involving chromosome 13 within 13q21.1q34, indicating trisomy for this region. Karyotype of POC could not be obtained due to the failure of the culture. The parental cytogenetic studies are recommended for associated balanced chromosomal rearrangements. Conclusion: Failure of the culture of POC especially in very early pregnancy loss is a common issue along with maternal and microbe contamination. CMA helps in overcoming these issues, as well as is useful in detecting very small structural chromosome aberrations such as microdeletions or microduplications. It is important to put in place evidence-based guidelines for managing early RPL in keeping with the available testing facilities, cost, and the awareness of patients and clinicians. A large country, like India, needs to discuss and develop consensus guidelines for genetic investigations in POC.